THE INFLUENCE OF PICTURE SERIES TOWARDS THE ABILITY OF THE EIGHTH GRADE STUDENTS OF SMP NEGERI 7 PANGKALAN KURAS IN WRITING NARRATIVE TEXTS - Darini, Rahma; ', Mahdum; K, Syafri. (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aimed to find out whether there isa significant influence of using picture series on students?ability of the VIIIgradeof SMP NEGERI 7 PangkalanKuras in the Academic Year 2015/2016 in writing narrative text. This is a pre-experimental research conducted by using a pre-test ? treatment ? post-test design. This research used one group pretest-posttest design.The instrument used in this research was tests (pretest and posttest). The population of this research was 102 of the Eighth Grade Students of SMP Negeri 7 PankalanKurasand the sample of this research is the VIII A of SMP Negeri 7 PangkalanKuras which is total number of students of class is 35 students. The data of this research were collected by giving the writing tests about narrative text (pretest-posttest) to the students. The collected data were analyzed by using t-test formula. The results of data analysis showed the mean score of pretest was 50.71, and the mean score of posttest was 60.57.Based on the data analysis, It can be concluded that there is a significant difference between the pre-test and the post-test because the t-test observed was higher than t-table. In other words, the alternative hypothesis of this researchwas accepted and null hypothesis was rejected.It also meant that teaching writing by using picture series technique was effectiveto improve students? writing ability especially in narrative text.Keywords : writing ability, picture series, narrative text